"The only good jihadist is a dead jihadist" : Boko Haram and de-radicalization around Lake Chad - (:unkn) unknown (My University, 2018)
This article discusses the shortcomings of the "de-radicalization doctrine" in sub-Saharan Africa. The issues raised are illustrated by the war against Boko Haram, which involves Nigeria, Niger, Chad and Cameroon. Relying on interviews with security officers, insurgents, civil servants, displaced people, humanitarian workers and Muslim and Christian clerics in Nigeria, Niger and Chad since 2005, the investigation shows that the four states focused on repression rather than demobilisation programs in prison or outdoors. The Boko Haram crisis is mainly a story of mismanagement. The article thus challenges the assumptions of the "de-radicalization doctrine" in Muslim Africa South of the Sahara. First, attempts to de-radicalize jihadi terrorists tend to focus too much on religious fanaticism and the exegesis of the Quran. Secondly, they are neither feasible nor efficient. Finally, they obscure priorities that are more important to counter extremism and demobilize insurgents.
Keywords: African Research